2015
DOI: 10.1189/jlb.4a0714-326r
|View full text |Cite
|
Sign up to set email alerts
|

NKG2D ligand overexpression in lupus nephritis correlates with increased NK cell activity and differentiation in kidneys but not in the periphery

Abstract: NK cells are a major component of the immune system, and alterations in their activity are correlated with various autoimmune diseases. In the present work, we observed an increased expression of the NKG2D ligand MICA in SLE patients' kidneys but not healthy subjects. We also show glomerulus-specific expression of the NKG2D ligands Rae-1 and Mult-1 in various murine SLE models, which correlated with a higher number of glomerular-infiltrating NK cells. As the role of NK cells in the immunopathogenesis of SLE is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 69 publications
3
51
0
1
Order By: Relevance
“…These differences are kidney specific, as neither bone marrow nor spleen NK cells from diseased mice show increased activity [77]. These data support the findings of Huang et al [42], who showed that kidney NK cells in mice with active disease produce more cytotoxic granules (perforin and granzyme B) and IFN-g than controls when stimulated with PMA + ionomycin; this increase in IFN-g production contributed, to some extent, to kidney damage in SLE [42,77]. These activated NK cells could be among the main IFN-g producers, responsible for promoting and sustaining inflammation in nephritic lupus kidney.…”
Section: Organ-specific Differences In Sle-looking In the Right Place?mentioning
confidence: 94%
See 2 more Smart Citations
“…These differences are kidney specific, as neither bone marrow nor spleen NK cells from diseased mice show increased activity [77]. These data support the findings of Huang et al [42], who showed that kidney NK cells in mice with active disease produce more cytotoxic granules (perforin and granzyme B) and IFN-g than controls when stimulated with PMA + ionomycin; this increase in IFN-g production contributed, to some extent, to kidney damage in SLE [42,77]. These activated NK cells could be among the main IFN-g producers, responsible for promoting and sustaining inflammation in nephritic lupus kidney.…”
Section: Organ-specific Differences In Sle-looking In the Right Place?mentioning
confidence: 94%
“…T-bet and Eomes are transcription factors that drive NK cell maturation and development locally and in the periphery and imprint the activated lymphoid program into these cells [89,90]. These differences are kidney specific, as neither bone marrow nor spleen NK cells from diseased mice show increased activity [77]. These data support the findings of Huang et al [42], who showed that kidney NK cells in mice with active disease produce more cytotoxic granules (perforin and granzyme B) and IFN-g than controls when stimulated with PMA + ionomycin; this increase in IFN-g production contributed, to some extent, to kidney damage in SLE [42,77].…”
Section: Organ-specific Differences In Sle-looking In the Right Place?mentioning
confidence: 97%
See 1 more Smart Citation
“…In this regard, an enhanced expression of NKG2D has been detected in CD3 + T cells from patients with SLE [20], which is apparently associated with chronic stimulation of these lymphocytes and an enhanced degradation of the CD3f (CD247) chain [21]. In addition, a significant expression of the NKG2D ligand MICA has been reported in kidneys from patients with SLE that is apparently associated with an enhanced local activation of NK cells [22].…”
Section: Introductionmentioning
confidence: 96%
“…However, for example, NK cells and their ligands are present in the kidney in human lupus nephritis (71). Experimentally, deficiency of invariant natural killer T cells exacerbated GN (72,73), while proinflammatory gd T cells are present in kidneys after passive antibody transfer (74).…”
Section: Innate Lymphoid Cells and Other T Lymphocytes: Unconventionamentioning
confidence: 99%